Brachial Plexus Injury Associated With Subclavian Vein Cannulation: A Case Report. Issue 7 (1st October 2017) - Gozubuyuk, Ezgi; Buget, Mehmet I.; Akgul, Turgut; Altun, Demet; Kuçukay, Suleyman
Abstract : We documented brachial plexus injury by electromyography and magnetic resonance imaging secondary to needle sticks for central line insertion. This type of complication is rare in the literature, as few case reports exist. Brachial plexus injury can happen because of anatomic variations. Nevertheless, multiple attempts or introducer needle rotations should be avoided during subclavian vein catheterization. Pain that emerges in the ipsilateral arm after subclavian catheter placement should be taken into serious consideration. It is important to identify the cause of pain as soon as possible so that the correct treatment can be efficiently provided. Use of an ultrasound-guided catheterization may be a better choice for preventing complications.